System dynamics model based on evolutionary game theory for quality supervision among construction stakeholders - Guo, Shengyu; Zhang, Pan; Yang, Jianying (Journal of Civil Engineering and Management, 2018)
To address the gap, that is, few studies have explored the influence of the participants’ interactions with one another during construction quality supervision, this paper proposes a system dynamics model based on evolutionary game theory to describe the complex and dynamic interactions among tripartite stakeholders in China, including the project owner (PO), construction supervising engineer (CSE), and construction contractor (CC). First, the replicated dynamic equation set is established in terms of expense targets. Second, the equilibrium solutions of the equation set are obtained to test strategy options. The trends of system fluctuations caused by penalty and reward changes are also analyzed. Finally, the stability of the proposed model is improved by integrating a dynamic penalty–reward scenario into the evolutionary strategy of the PO. Simulation results show that: 1) the evolutionary stable strategy does not exist in initial interactions, 2) the degrees of penalty and reward considerably affect the CC’s rate variable, and 3) the dynamic penalty–reward scenario could effectively improve the stability of the proposed model. The unsteadiness of the quality supervision system and the stability control scenario could help in understanding the impact of interactions among stakeholders and provide suggestions for optimizing quality supervision procedures.